Life dissatisfaction among students: Exploring the role of intrapersonal conflict, insufficient efforts and academic stress - Anju; Amandeep; B. K. Punia; Vandana Punia; Naval Garg (Rajagiri Management Journal (RAMJ), 2021)
Purpose: The study focuses on academic stress among the students due to insufficient efforts and intrapersonal conflicts amid the COVID-19 situation. The purpose of this study is to measure the mediating role of academic stress between life dissatisfaction and adequate steps and intrapersonal conflicts. Design/methodology/approach: The researcher had surveyed 729 students from the two states, including Haryana and Punjab and 716 responses were used for analysis. These respondents were approached in April-May 2020 to explore the impact of COVID-19. The questionnaire was prepared with the help of Google form, including 29 questions. Confirmatory factor analysis and structural equation modeling (SEM) were used to validate the research model and for testing the hypothesis. Findings: The findings indicate that intra-personal conflict and insufficient efforts have a significant positive relation with academic stress. Also, intrapersonal conflict and insufficient efforts have a significant positive relation with life dissatisfaction. It has been reported that academic stress mediates the relationship between life dissatisfaction and intra-personal conflict. The results also reveal that academic stress is positively and significantly associated with life dissatisfaction. Originality/value: This is one of the few studies that explored the mediating role of academic stress between life dissatisfaction and insufficient efforts and intrapersonal conflicts.
Keywords: 650; Academic stress; Life dissatisfaction; Insufficient efforts; Intrapersonal conflicts